Some Epidemiological Aspects of Infections of Urinary Tract in patients of Altai Regional Hospital for Veterans of Wars - K. I. Sursyakova; T. V. Safyanova (Эпидемиология и вакцинопрофилактика, 2019)
Background. Urinary tract infections (UTIs) are among the most common infectious diseases in outpatient and hospital practice.Goals: was to identify the epidemiological aspects of UTI among the patients of «Altai regional hospital for veterans of wars» (AKGVV).Methodology. AKGVV: is a multi-specialized medical institution. The structure of which includes an advisory-polyclinic department for 180 visits per shift and a hospital for 305 beds of round-the-clock stay. A retrospective analysis of the incidence of UTI in AKGVV was carried out. During the analysis, the data of the information system «Hospital» for 2008–2017 were used. The study materials were subjected to statistical processing. The statistical analysis was carried out with the help of programs STATISTICA 10.0 and MSExcel 2010.Results. From 2012 there was a tendency to reduce the dynamics of incidence of UTI. In the dynamics of incidence of chronic cystitis, there was a tendency to reduce it. In the dynamics of the incidence of chronic pyelonephritis, there was also a tendency to decrease. There was a sporadic incidence of acute pyelonephritis .1 case of acute cystitis incidence recorded in 2010. In the structure of patients with UTI, patients from 80 years and older – 57.70%; patients aged 70–79 years accounted for 20.59%, 60–69 years – 15.29%..Сonclusions The average severity (81.2%) prevailed in the structure of patients with UTI, which requires special approach of medical personnel to care of patients, ensuring proper sanitary and anti-epidemic regimen in hospital departments and selection of antibacterial therapy.